Charge-transfer mediated nanopore-controlled pyrene derivatives/graphene colloids. (November 2018) - Putri, Austina D.; Chotimah, Nurul; Ujjain, Sanjeev Kumar; Wang, Shuwen; Futamura, Ryusuke; Vallejos-Burgos, Fernando; Khoerunnisa, Fitri; Morimoto, Masafumi; Wang, Zhipeng; Hattori, Yoshiyuki; Sakai, Toshio; Kaneko, Katsumi
Abstract: Electrically-conductive graphene colloids with tuned nanoporosity are promising materials for numerous applications. As charge-transfer interaction enhances electrical conductivity of polyaromatic hydrocarbon crystals, we intercalated water-soluble pyrene derivatives such as pyrene-boronic acid in nanoporous graphene by reduction of a mixture of graphene oxides and pyrene derivatives. The pyrene derivative intercalation increases more than twice both microporosity and mesoporosity. The N2 adsorption isotherms at 77 K of all samples have low-pressure adsorption hysteresis due to inaccessible small microporosity; the total porosity evaluated by water adsorption at 298 K is almost twice that of N2 adsorption. These adsorption measurements together with X-ray diffraction suggest the presence of a pore mouth structure whose width is about 0.4 nm. The charge-transfer interaction between the pyrene derivative and porous graphene is evidenced by a high frequency shift of the G band of Raman spectrum, appearance of a new optical absorption band, and the increase in electrical conductivity. The intercalation of pyrene-boronic acid through charge-transfer interaction increases the voltammetric charge of cyclic voltammogram for nanoporous graphene owing to an enhanced ion-accessibility from 3% to 54%, which indicates their high application potential for electrochemical studies. Graphical abstract: Image 1